On Soft-Biometric Information Stored in Biometric Face Embeddings - Terhörst, Philipp; Fährmann, Daniel; Damer, Naser; Kirchbuchner, Florian; Kuijper, Arjan (IEEE Trans. Biom. Behav. Identity Sci.)

PROJECT FOR THE DEVELOPMENT OF OPERATIONAL AND DEMAND-ORIENTED FIREFIGHTING EQUIPMENT - Hanses, Hendrik; Horwath, Ilona (Book of Abstracts 37th Danubia Adria Symposium on Advances in Experimental Mechanics)

Longitudinal mechanical joining of extruded aluminium profiles with increased tightness requirements - Neumann, Stefan; Meschut, Gerson; Kneuper, Florian; Hering, Oliver; Tekkaya, Erman

Herrscherhuldigung und Friedenslob – Das Opusculum cantionum des Johannes Flamingus (1571) - Höink, Dominik (Religiöse Friedensmusik von der Antike bis zur Gegenwart)

Frieden – Musik – Religion: Zur Einführung - Höink, Dominik (Religiöse Friedensmusik von der Antike bis zur Gegenwart)

Religiöse Friedensmusik von der Antike bis zur Gegenwart
Musik war seit jeher ein zentrales Medium der künstlerischen Auseinandersetzung mit dem Thema „Frieden“. Ob als gesungene Friedensbitte innerhalb von religiösen Zeremonien, als Mittel zur Formulierung von Friedenssehnsucht oder als Teil von Feierlichkeiten nach einem Friedensschluss – unzählige Beispiele aus den verschiedensten kulturellen Kontexten und Zeiten wären anzuführen. Die Beiträge im vorliegenden Band, die auf eine Tagung im Juni 2018 in Münster zurückgehen, thematisieren daher sowohl innerkompositorische Friedensbezüge als auch kontextbedingte Zuschreibungen, die sich etwa aus der Funktionalisierung für entsprechende Friedensfeiern ergeben. Durch den historischen Längsschnitt und den Einschluss von Beiträgen zur außereuropäischen und nicht-christlichen Musik ergibt sich ein weites Panorama unterschiedlichster Studien.

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Collaborating with Virtual Assistants in Organizations: Analyzing Social Loafing Tendencies and Responsibility Attribution - Stieglitz, Stefan; Mirbabaie, Milad; Möllmann, Nicholas R. J.; Rzyski, Jannik (Information Systems Frontiers)
Abstract Organizations increasingly introduce collaborative technologies in form of virtual assistants (VAs) to save valuable resources, especially when employees are assisted with work-related tasks. However, the effect of VAs on virtual teams and collaboration remains uncertain, particularly whether employees show social loafing (SL) tendencies, i.e., applying less effort for collective tasks compared to working alone. While extant research indicates that VAs collaboratively working in teams exert greater results, less is known about SL in virtual collaboration and how responsibility attribution alters. An online experiment with N = 102 was conducted in which participants were assisted by a VA in solving a task. The results indicate SL tendencies in virtual collaboration with VAs and that participants tend to cede responsibility to the VA. This study makes a first foray and extends the information systems (IS) literature by analyzing SL and responsibility attribution thus updates our knowledge on virtual collaboration with VAs.
Keywords: Computer Networks and Communications; Information Systems; Theoretical Computer Science; Software

The rise of artificial intelligence – understanding the AI identity threat at the workplace - Mirbabaie, Milad; Brünker, Felix; Möllmann Frick, Nicholas R. J.; Stieglitz, Stefan (Electronic Markets)
Abstract Artificial intelligence (AI) is being increasingly integrated into enterprises to foster collaboration within humanmachine teams and assist employees with work-related tasks. However, introducing AI may negatively impact employees’ identifications with their jobs as AI is expected to fundamentally change workplaces and professions, feeding into individuals’ fears of being replaced. To broaden the understanding of the AI identity threat, the findings of this study reveal three central predictors for AI identity threat in the workplace: changes to work, loss of status position, and AI identity predicting AI identity threat in the workplace. This study enriches information systems literature by extending our understanding of collaboration with AI in the workplace to drive future research in this field. Researchers and practitioners understand the implications of employees’ identity when collaborating with AI and comprehend which factors are relevant when introducing AI in the workplace.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Is it alright to use artificial intelligence in digital health? A systematic literature review on ethical considerations - Möllmann, Nicholas RJ; Mirbabaie, Milad; Stieglitz, Stefan (Health Informatics Journal)
The application of artificial intelligence (AI) not only yields in advantages for healthcare but raises several ethical questions. Extant research on ethical considerations of AI in digital health is quite sparse and a holistic overview is lacking. A systematic literature review searching across 853 peer-reviewed journals and conferences yielded in 50 relevant articles categorized in five major ethical principles: beneficence, non-maleficence, autonomy, justice, and explicability. The ethical landscape of AI in digital health is portrayed including a snapshot guiding future development. The status quo highlights potential areas with little empirical but required research. Less explored areas with remaining ethical questions are validated and guide scholars’ efforts by outlining an overview of addressed ethical principles and intensity of studies including correlations. Practitioners understand novel questions AI raises eventually leading to properly regulated implementations and further comprehend that society is on its way from supporting technologies to autonomous decision-making systems.
Keywords: Health Informatics